Land Resources Management for Sustainable Production and Environment Protection - Suraj Bhan (Journal of Soil and Water Conservation, 2022)
Intensive agriculture will sustain only when adequate supplies of water, whether through rainfall, surface sources or underground sources, are made available. The future of our agriculture depends upon the padicrous use of our water resources. The most important and the baste natural resource is soul, Soil is a finite, non-elastic and non-renewable asset, The production of food, fodder, fuel and feeds to supply the requirements of our human and animal population is dependent upon agriculture and allied pursuits which are dependent on soul resources. The per capita availability of land has already decreased from 0.5 ha. in 1950-51 to 0.15 ha. in 1999-2000 and would further reduce to 0.08 ha, in 2020. The role of agriculture covering crops, animal husbandry, dairying and fisheries, in generating broad-based economic growth is evident from the fact that this sector contributes nearly 1/3tothegross domestic product (GDP). Irrigated, Coastal, And, Rainfed and Hull & Mountainous are five agro-ecosystems in India which have been defined in the present study. Soil, water and air pollutions, which are on the increase, are hampering crop production, human and animal health and eroding biodiversity. Concentrated efforts are needed to protect the natural resource from pollution to sustain agricultural productivity through establishing appropriate vegetative cover and by installing gadgets, which will reduce pollution from industrial activities. Our farming practices need to be oriented to wands eco-friendly nature to save our natural resources and mother earth. The data base on soil and water resources, appropriate tillage, Irrigation, manures and fertilization practices, IPM, INM, IWM including use of biofertihzers, organic manures, vermicompost etc., afforestation, policy measures to arrest soul erosion, proper water management practices, effective utilization of water resources etc. have been focused in this study for immediate attention for promoting conservation of natural resources for sustainable development and environment protection.